The Effect of Self-Efficacy on Turnover Intention Through Work-Life Balance As A Mediation (Study on Employees of The Faculty of Economics and Business, Udayana University) - I Putu Nugraha Wira Pratama; Ida Bagus Ketut Surya (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the role of work-life balance in mediating the effect of self-efficacy on turnover intention. The research employed a saturated sampling technique with a sample of 112 employees. The method used was a survey method with questionnaires and interviews, analyzed using descriptive statistics and inferential statistical analysis with SEM-PLS. The results of this study indicate that self-efficacy has a negative effect on turnover intention. Self-efficacy has a positive and significant effect on work-life balance. Work-life balance negatively affects turnover intention. Furthermore, work-life balance is able to mediate the effect of self-efficacy on turnover intention. The theoretical implication of this research is a confirmation of attribution theory and its relation to the research variables. The practical implication provides alternative solutions to the problem of turnover intention. The recommendation given is that the Faculty of Economics and Business, Udayana University, should provide psychological support and a conducive work environment to enhance employees’ self-efficacy, while also developing flexible work policies that support work-life balance through workload management, rest periods, and a work culture that respects personal life.